Did Climate Change Influence the Emergence, Transmission, and Expression of the COVID-19 Pandemic? - Gupta, Saloni; Rouse, Barry T.; Sarangi, Pranita P. (Frontiers in Medicine, 2021)
The human race has survived many epidemics and pandemics that have emerged and reemerged throughout history. The novel coronavirus Severe Acute Respiratory Syndrome SARS-CoV-2/COVID-19 is the latest pandemic and this has caused major health and socioeconomic problems in almost all communities of the world. The origin of the virus is still in dispute, but most likely the virus emerged from the bats and also may have involved an intermediate host before affecting humans. Several other factors also may have affected the emergence and outcome of the infection, but in this review we make a case for a possible role of climate change. The rise in industrialization-related human activities has created a marked imbalance in the homeostasis of environmental factors such as temperature and other weather and these might even have imposed conditions for the emergence of future coronavirus cycles. An attempt is made in this review to explore the effect of ongoing climate changes and discuss if these changes had a role in facilitating the emergence, transmission, and even the expression of the COVID-19 pandemic. We surmise that pandemics will be more frequent in the future and more severely impactful unless climate changes are mitigated.